Coating Nanoparticles with Gastric Epithelial Cell Membrane for Targeted Antibiotic Delivery against Helicobacter pylori Infection. Issue 2 (8th May 2018) - Angsantikul, Pavimol; Thamphiwatana, Soracha; Zhang, Qiangzhe; Spiekermann, Kevin; Zhuang, Jia; Fang, Ronnie H.; Gao, Weiwei; Obonyo, Marygorret; Zhang, Liangfang
Abstract: Inspired by the natural pathogen–host interactions and adhesion, this study reports on the development of a novel targeted nanotherapeutic for the treatment of Helicobacter pylori infection. Specifically, plasma membranes of gastric epithelial cells (e.g., AGS cells) are collected and coated onto antibiotic‐loaded polymeric cores; the resulting biomimetic nanoparticles (denoted AGS‐NPs) bear the same surface antigens as the source AGS cells and thus have inherent adhesion to H. pylori bacteria. When incubated with H. pylori bacteria in vitro, the AGS‐NPs preferentially accumulate on the bacterial surfaces. Using clarithromycin (CLR) as a model antibiotic and a mouse model of H. pylori infection, the CLR‐loaded AGS‐NPs demonstrate superior therapeutic efficacy when compared with the free drug counterpart as well as a non‐targeted nanoparticle control group. Overall, this work illustrates the promise and strength of using natural host cell membranes to functionalize drug nanocarriers for targeted drug delivery to pathogens that colonize on the host cells. As host–pathogen adhesion represents a common biological event for various types of pathogenic bacteria, the bioinspired nanotherapeutic strategy reported here represents a versatile delivery platform that may be applied to treat numerous infectious diseases. Abstract : An active targeting approach is reported for effective antibiotic delivery to Helicobacter pylori bacteria by mimicking and leveraging the natural pathogen–host binding interactions . Specifically, gastric epithelial cell membrane is collected and cloaked onto antibiotic‐loaded polymeric nanoparticles. The resulting biomimetic nanotherapeutics show superior bactericidal effects in vitro and significantly reduce the bacterial burden in a mouse model of H. pylori infection.